An eye tracking comparison of external pointing cues and internal continuous cues in learning with complex animations - Lowe, Ric; Boucheix, J. (Pergamon, 2010)
Two experiments used eye tracking to investigate a novel cueing approach for directing learner attention to low salience, high relevance aspects of a complex animation. In the first experiment, comprehension of a piano mechanism animation containing spreading-colour cues was compared with comprehension obtained with arrow cues or no cues. Eye tracking data revealed differences in learner attention patterns between the different experimental conditions. The second experiment used eye tracking with synchronized and non-synchronized cues to investigate the role of dynamic direction of attention in cueing effectiveness. Results of Experiment 1 showed that spreading-colour cues resulted in better targeting of attention to thematically relevant aspects and in higher comprehension scores than arrow cues or no cues. For Experiment 2, superior comprehension after the synchronized version together with eye tracking data indicated that cue effectiveness depended on attention direction being spatially and temporally coordinated with onsets of animation events having high thematic relevance to the learning task. The findings suggest the importance of perceptual cues and bottom-up processing.